WATER IN THE PROCESS OF CREATING THE RANGDA MASK BY TJOKORDA OKA TUBLEN - Cokorda Alit Artawan; A.A Dwi Dirgantini (UPT Pusat Penerbitan LP2MPP ISI Bali, 2022)
This study aims to profoundly understand the role of water in creating the Rangda Mask by Tjokorda Oka Tublen Singapadu Gianyar. In creating the Rangda mask, water is one of the most important means of a “sekala niskala.” However, until now, there has been no in-depth study of water’s role in creating the Rangda Mask. Therefore, the questions are: (1) What is water’s role in making the Rangda Mask by Tjokorda Oka Tublen? (2) What is the process of making the Rangda Mask by Tjokorda Oka Tublen? This research uses a qualitative approach to analyze the phenomena related to the process of its creation. The data source comes from Topeng Rangda by Tjokorda Oka Tublen (the sangging, artists) using purposive sampling and snowball. The data collection technique uses observation, interviews, and document studies. As well as solving the problem using the theories of the creation process as the leading theory and supported by aesthetic and functional, structural theory, the research results show that: (1) Water has a vital role in creating the Rangda Mask on a sekala-niskala. Regularly, water is used as a cleanser for the maker’s body and tools. In contrast, niskala water is used as tirtha (holy water) for ritual purification. (2) The process of creation is taken through several stages: newasen, nyalonan, makalan, nadiang, nelesang, ngalusang, ngewarna, and pasupati. Finally, after all the stages are passed, the Rangda mask that is sacred and profane is realized.